EFEKTIVITAS MODEL PEMBELAJARAN PILIHAN AKTIVITAS BELAJAR (PAB) DALAM IMPLEMENTASI KURIKULUM MERDEKA SISWA KELAS 4 SDN PORIS PELAWAD 5 KOTA TANGERANG - Ina Magdalena; Lisa Denanda Putri; Rihlah Hasanah (CV. ADIBA AISHA AMIRA, 2023)
This study aims to determine the effectiveness of the Learning Activity Choice (PAB) learning model that has been developed previously. The method used is the Think, Pair, Share (TPS) method, the Jigsaw Learning Method, the Project Based Learning Method. The learning method will assist teachers in managing the classroom. The presence of learning methods will affect the learning activities of students so that they can be more conducive. Effective learning can be realized when the basic needs of all students are considered in planning, implementing, and assessing learning. The results of learning acquistion achieved by students after being involved in interaction with learning resources.